Field study on the safety and efficacy of intradermal versus intramuscular vaccination against Mycoplasma hyopneumoniae. (30th September 2017) - Beffort, Lisa; Weiß, Christine; Fiebig, Kerstin; Jolie, Rika; Ritzmann, Mathias; Eddicks, Matthias
Abstract : The present study compares the safety and efficacy of a needle‐free, intradermal Mycoplasma hyopneumoniae vaccine to an intramuscular one. 420 piglets (21+3 days of age) were randomly assigned to two vaccination groups (intradermal vaccination V1 (n=138), intramuscular vaccination V2 (n=144)) and one unvaccinated control group (CG, n=138). As safety parameters clinical observations, local injection site reactions (ISR) and rectal temperatures were assessed. Average daily weight gain (ADWG) and pneumonic lung lesions (LL) were measured as efficacy parameters. ISRs were minor in V1. After both vaccinations, no adverse impact on appetite was observed and mean rectal temperatures remained within physiological range. ADWG during the fattening period was significantly higher in vaccinated groups (V1: 913.4 g, V2: 924.5 g) compared with CG (875.6 g). No differences in ADWG were observed between V1 and V2. Vaccinated pigs had a significantly reduced mean extent of LL compared with CG. V1 was superior in reducing the extent and prevalence of LL compared with V2. These results reveal that a needle‐free intradermal vaccination is safe and efficacious in reducing both the prevalence and extent of lung lesions, as well as in improving performance parameters, in a farrow‐to‐finish farm with a late onset of M hyopneumonia e infection.